PELUANG PASAR GLOBAL PIZZA HUT - Suprapto, Yandi; Evelyn, Evelyn; Yang, Jenny; Yuki, Narumi; Wenny, Wenny (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
Frequent marketing activities are also classy marketing work done all over theplace. Global marketing opportunities exist for all entrepreneurs who can channeltheir innovation and creativity into emerging markets. Pizza Hut is a restaurantthat was founded in 1958. This business first entered Indonesia in 1984, and it wasalso the first pizza restaurant in Indonesia at the time. The author's goal in carryingout this analysis is that pizza is an Italian dish that is very well known everywherewith a very unique and varied taste image, which is of course very popular withIndonesians. Based on the results of the analysis, there are six tasks in the globalmarket.